The role of central bank knowledge and trust for the public's inflation expectations - Sathya Mellina; Tobias Schmidt (Deutsche Bundesbank, 2018)
Since the financial crisis, central banks have stressed the role of trust and communication in connection with their objectives and strategies for aligning the public's inflation expectations with their own and, consequently, improving the effectiveness of monetary policy. Assessing how much the general public knows about and trust in central banks and how these factors influence inflation expectations is thus important. We shed light on these issues by relying on a representative survey conducted among individuals living in Germany. Although most respondents assume that they have a good or very good knowledge of the ECB and the Bundesbank, only about 20 percent cite "price stability" when asked directly about the two central banks' objectives. Knowledge of the ECB's and the Bundesbank's goals act as significant drivers of trust in these institutions, however. And greater trust in the ECB and Bundesbank, in turn, lowers individuals' inflation expectations. More specifically, having greater trust increases the probability of expecting unchanged prices and decreases the likelihood of expecting either slightly or sharply rising prices over the medium term. Interestingly, awareness of price stability as the primary objective of the ECB's monetary policy does not seem to affect inflation expectations directly once we control for trust, individuals' socio-demographic characteristics and their interest in economic topics. Our study indicates that central banks can influence households' inflation expectations through building trust and educating the public about their targets.
Keywords: D12; D84; E52; E58; 330; Inflation Expectations; Trust; Economic Knowledge; Central Bank Communications; European Central Bank; Deutsche Bundesbank